For what real value of x , the numbers: lo g 1 7 8 , lo g 8 1 ( 2 x + 2 ∗ 3 x ) , x lo g 3 in the order that provided are in arithmetic progression?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If the numbers a , b and c are in arithmetic progression, it follows that b − a = c − b . Also, a logarithm property states that lo g a − lo g b = lo g b a .
It all comes down to:
lo g 1 7 8 8 1 ( 2 x + 2 × 3 x ) = lo g 8 1 ( 2 x + 2 × 3 x ) 3 x ⇒ 1 7 8 8 1 ( 2 x + 2 × 3 x ) = 8 1 ( 2 x + 2 × 3 x ) 3 x
⇒ 1 7 8 × 3 x = 8 1 × 2 x + 1 6 2 × 3 x ⇒ 1 6 × 3 x = 8 1 × 2 x
⇒ 8 1 3 x = 1 6 2 x ⇒ 3 x − 4 = 2 x − 4 .
A generic form of this last equation is a c = b c , where a and b are constants and c is the variable. For a = b , it will only be true for c = 0 .
Thus, x − 4 = 0 ⇒ x = 4 .
Problem Loading...
Note Loading...
Set Loading...
We should use here the formula lo g ( n m ) = lo g m − lo g n and m lo g n = lo g m n . For the terms lo g 1 7 8 , lo g 8 1 ( 2 x + 2 × 3 x ) , x lo g 3 to be in AP, then the difference of the consecutive terms should be same i.e,
lo g 8 1 ( 2 x + 2 × 3 x ) − lo g 1 7 8 = x lo g 3 − lo g 8 1 ( 2 x + 2 × 3 x )
⟹ lo g ( 1 7 8 8 1 ( 2 x + 2 × 3 x ) ) = lo g 3 x − lo g 8 1 ( 2 x + 2 × 3 x )
⟹ lo g ( 1 7 8 8 1 ( 2 x + 2 × 3 x ) ) = lo g ( 8 1 ( 2 x + 2 × 3 x ) 3 x )
Applying antilog, we get---
1 7 8 8 1 ( 2 x + 2 × 3 x ) = 8 1 ( 2 x + 2 × 3 x ) 3 x
⟹ 1 7 8 × 3 x = 8 1 ( 2 x + 2 × 3 x )
⟹ 1 7 8 × 3 x = 8 1 × 2 x + 1 6 2 × 3 x
⟹ 1 6 × 3 x = 8 1 × 2 x
⟹ 3 x 2 x = 8 1 1 6 = 3 4 2 4
⟹ ( 3 2 ) x = ( 3 2 ) 4
Comparing both sides, we get ----
x = 4